2023
DOI: 10.3390/ijms242316726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Associated with Suicide

Daniela Navarro,
Marta Marín-Mayor,
Ani Gasparyan
et al.

Abstract: Suicide is a serious global public health problem, with a worrying recent increase in suicide rates in both adolescent and adult populations. However, it is essential to recognize that suicide is preventable. A myriad of factors contributes to an individual’s vulnerability to suicide. These factors include various potential causes, from psychiatric disorders to genetic and epigenetic alterations. These changes can induce dysfunctions in crucial systems such as the serotonergic, cannabinoid, and hypothalamic–pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 219 publications
(301 reference statements)
0
0
0
Order By: Relevance
“…Next, future studies ought to utilize comprehensive community- and family-based evaluation approaches, and systematically study potential neuroimaging and peripheral biomarkers that can predict different suicide behaviors (i.e., suicide ideation versus attempts versus completion). For example, previous research has found abnormalities in the hypothalamic-pituitary-adrenal (HPA) axis and serotonergic systems in suicide completers ( 12 ), as well as differences in prefrontal circuitry between suicide attempters and nonsuicidal patients were discovered on brain imaging ( 13 , 14 ). Investigating how the stress response system (HPA axis) behaves differentially, the evolution of a growing brain in adapting to the various stressors, and the identification of authentic biomarkers that can predict suicidal behaviors can help provide further pathophysiologic clues to the intriguing gender paradox puzzle in adolescents.…”
Section: Main Textmentioning
confidence: 99%
“…Next, future studies ought to utilize comprehensive community- and family-based evaluation approaches, and systematically study potential neuroimaging and peripheral biomarkers that can predict different suicide behaviors (i.e., suicide ideation versus attempts versus completion). For example, previous research has found abnormalities in the hypothalamic-pituitary-adrenal (HPA) axis and serotonergic systems in suicide completers ( 12 ), as well as differences in prefrontal circuitry between suicide attempters and nonsuicidal patients were discovered on brain imaging ( 13 , 14 ). Investigating how the stress response system (HPA axis) behaves differentially, the evolution of a growing brain in adapting to the various stressors, and the identification of authentic biomarkers that can predict suicidal behaviors can help provide further pathophysiologic clues to the intriguing gender paradox puzzle in adolescents.…”
Section: Main Textmentioning
confidence: 99%